COLLABORATIVE GOVERNANCE PERLINDUNGAN LAHAN PERTANIAN DALAM IMPLEMENTASI UNDANG- UNDANG TENTANG PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN (PLP2B) - Angga, I Made Prastika (Universitas Muhammadiyah Sumatera Utara, 2024)
The Indonesian government has enacted Law No. 41/2009 on the Protection of Sustainable Food Agricultural Land as a government decree that aims to protect agricultural land from the problem of land conversion that continues to increase every year. This agricultural land protection policy is the basis for decisions in controlling land conversion. The purpose of this research is to find out the Collaborative Governance of the implementation of agricultural land protection policies in Indonesia. This research uses a qualitative research method with a literature review approach through online search sources through Google Scholar. The result of this research is the Implementation of Agricultural Land Protection Program in Indonesia, currently still not implemented and running effectively and the lack of collaboration or cooperation between stakeholders in several regions in Indonesia. For this reason, there needs to be an effort through the Collaborative Governance approach or requires cooperation between the government as a regulator, the private sector, and the community, especially the landowners and farmers so that the implementation of this program runs well according to the objectives of the policy setting. Keywords: Collaborative Governance, Policy Implementation, Agricultural Land Protection